Transformations of Liberal Reason: Migration Politics and Shifts in Cultural Self-Interpretation - Kaufmann, Hannes; Justus Liebig University Giessen (My University, 2020)
In light of the current multiple crises, authoritarian movements gain new strength. Claiming that globalization and especially migration is endangering social cohesion and national sovereignty, without considering political-economic aspects, they call for a strong state. Along the lines of those claims, they revise what Helmut Dubiel called the cultural selfinterpretation, meaning the understanding of the political super-structure of their community. Doing that, liberal values and concepts are re-inter-preted, as can be seen with the rule of law for example. From its intrinsic value of strengthening individual claims against the state s rule, they turn it into a concept of state power, interpreting the rule of law as the rule of a mythical legitimized sover-eign. Those re-interpretations and legal constructs referring to them will be an-alyzed in this essay. Authoritarian politics and their roots will be regarded in their contradictory relation to (neo-)liberalism as they appear as a critique towards it at first glance. Yet, taking into account early Critical Theory and its analysis of authoritarian-ism, the article aims to show that those tendencies emerge from liberal ideas and ide-als. Seen from this perspective the article promotes the view that rather than a pure defense of liberalism, a materialist examination of liberalism s inner contradictions is necessary to understand and criticize authoritarianism.
Keywords: authoritarianism; Critical Theory; law; (neo-)liberalism; sovereignty; ddc:300